Original researchPerfusion assessed by real-time contrast echocardiography correlates with clinical and echocardiographic parameters in patients with first STEMI treated with PCI – 6-month follow-up - Tomaszuk-Kazberuk, Anna; Sobkowicz, Bozena; Dobrzycki, Slawomir; Lewczuk, Anna; Musial, Wlodzimierz (Archives of Medical Science, 2010)
Introduction: Angiographic flow in an epicardial artery does not define perfusion at a microvascular level in patients with acute myocardial infarction (AMI). The aim of the study was assessing microvascular reperfusion by myocardial contrast echocardiography (MCE) and left ventricular (LV) functional recovery by echocardiographic methods in patients treated with primary PTCA. Material and methods: 100 consecutive patients with first ST-elevation AMI with single vessel disease treated successfully with primary PCI were enrolled. Regional contrast score index (RCSI), ejection fraction (EF), wall motion score index (WMSI), and end-systolic and end-diastolic volume (ESV, EDV) were evaluated during hospitalization and at 6-month follow-up. The patients were divided into 2 groups according to the absence (Group 1) or presence (Group 2) of perfusion defects on MCE. Results: Group 1 had lower WMSI (p = 0.0009), higher EF than Group 2 (44.7 and 55.9% respectively, p = 0.000067), and lower ESV (66.0 and 52.6 ml respectively, p = 0.003185). In Group 1 LVEF increased significantly on 6-month follow-up (p = 0.026), while in Group 2 it decreased (p = 0.0175). Both EDV and ESV were significantly lower in Group 1 (p = 0.0106 and p = 0.002882, respectively). There was a correlation between the presence of perfusion defects in the initial contrast echo and unfavourable change in ejection fraction during the follow-up (ANOVA for repeated measures, F[1.91] = 5.85, p = 0.0175). The combined clinical end-point (death and reinfarction) was significantly lower in patients without perfusion defect (p = 0.039). Conclusions: Myocardial contrast echocardiography results correlated with clinical outcome and recovery of systolic left ventricular function at 6-month follow-up.